Social elites can emerge naturally when interaction in networks is restricted - David-Barrett, T; Dunbar, R (Oxford University Press, 2014)
Animal (and human) societies characterized by dominance hierarchies invariably suffer from inequality. The rise of inequality has 3 main prerequisites: 1) a group in which inequality can emerge, 2) the existence of differences in payoff, and 3) a mechanism that initiates, accumulates, and propagates the differences. Hitherto, 2 kinds of models have been used to study the processes involved. In winner-loser models of inequality (typical in zoology), the 3 elements are independent. In division-of-labor models of inequality, the first 2 elements are linked, whereas the third is independent. In this article, we propose a new model, that of synchronized group action, in which all 3 elements are linked. Under these conditions, agent-based simulations of communal action in multilayered communities naturally give rise to endogenous status, emergent social stratification, and the rise of elite cliques. We show that our 3 emergent social phenomena (status, stratification, and elite formation) react to natural variations in merit (the capacity to influence others' decisions). We also show that the group-level efficiency and inequality consequences of these emergent phenomena define a space for social institutions that optimize efficiency gain in some fitness-related respect, while controlling the loss of efficiency and equality in other respects. © The Author 2013.